Defense energy resilience lessons from ecology - Thomas, Scott; Kerner, David (Strategic Studies Institute, U.S. Army War College, 2010)
National security relies heavily on the ready availability of energy resources in the types, quantities, and locations the military demands. While U.S. energy needs are currently met, the shrinking gap between global supply and demand draws the world closer to a tipping point at which human behavior is less predictable, competition overwhelms social and geopolitical normalizing forces, and conflict becomes more likely and more pronounced. Given concerns about future resource availability, DoD would be well served by devising and implementing a sustainable, resilient energy strategy that addresses current projections and adapts to evolving conditions
"August 2010."
Includes bibliographical references (p. 35-43)
Introduction to the problem -- A new theoretical perspective -- Resilience theory -- Adaptive management -- Benefits and risks of adaptive management -- Discussion : enhancing energy security based on a resilience perspective -- Application -- Action plan -- Conclusions and recommendations
Keywords: United States / Dept. of Defense / Energy consumption; Energy policy / United States; Petroleum industry and trade / United States; Renewable energy sources / United States; Adaptive natural resource management / United States; Energy conservation / United States; Human ecology / United States; National security / United States; USA